In Vitro Analysis and Assessment of the Bioavailability of Selected Minerals and B Vitamins in Kefir Enriched with Microalgae - Łukasz Byczyński; Robert Duliński; Sylwester Smoleń (Applied Sciences, 2025)
In the presented work, an attempt was made to digest kefir enriched with microalgae additives from the species Arthrospira platensis and Chlorella pyrenoidosa in four concentrations—0.1, 0.5, 1, and 5%. The level of released protein, phosphorus, iron, iodine, and selected vitamins from the B group was analyzed, and their bioavailability was additionally estimated. The amount of iron released in these conditions increased significantly from 0.1% of the supplementation level. Higher values of iron were obtained for Chlorella, and in the case of protein, slightly higher values were noted for Spirulina. In turn, for vitamin B2, higher amounts were noted for Chlorella for doses of 1 and 5%. In the case of vitamin B12, significantly higher amounts were noted in the case of Spirulina supplementation. After in vitro digestion, an increase in the bioavailability of protein and phosphorus was observed with an increase in the dose of microalgae. The relative bioavailability of iron decreased with an increase in the dose of microalgae used, similarly to vitamin B12. Chlorella was characterized by higher iron bioavailability than Spirulina, and in the case of vitamin B2 only at the highest doses of 1 and 5% of the algal supplement. The tests carried out show that microalgae supplementation significantly increases the content of protein, phosphorus, iron, and vitamin B12 in the tested kefir.